Datasets:
Tasks:
Text Generation
Modalities:
Text
Sub-tasks:
language-modeling
Languages:
English
Size:
100K - 1M
License:
import data.real.nnreal | |
import topology.algebra.infinite_sum | |
import analysis.normed_space.basic | |
import for_mathlib.nnreal | |
import for_mathlib.nnreal_int_binary -- basic binary expansion for nnreal. | |
open_locale nnreal | |
/- | |
# Two auxiliary lemmas. | |
In this file we prove two technical lemmas, needed in the proofs of parts (2) and (4) | |
of Proposition 7.2 of `Analytic.pdf`. | |
## Lemma 1 (needed in part 2) | |
Say `f : ℤ → ℝ` and `r : ℝ≥0` with `2⁻¹<r<1`. | |
Say the support of `f` is bounded below by `d` (i.e. `n < d → f n = 0`), | |
We think of `f` as a power series `∑ₙf(n)Tⁿ` in `ℤ⟦T⟧[T⁻¹]`. | |
Here's the set-up. Support that `∑' (n : ℤ), ∥f n∥₊ * r ^ n` converges and is `≤ c` | |
(so in particular `f(T)` converges for `∥T∥ ≤ c`). Suppose also that | |
`∑' (n : ℤ), f n * 2⁻¹ ^ n = 0` (so `f` has a zero at `2⁻¹`; note that the sum | |
converges because `0 ≤ 2⁻¹ < r`). | |
The conclusion is that `∑(n ≥ d) ∥∑(0≤i≤(n-d)) f(n - 1 - i)*2ⁱ∥ * r^n` | |
also converges and is bounded above by `c * (2 - r⁻¹)⁻¹`. | |
The power series `∑(n≥d) (∑(0≤i≤(n-d)) f(n - 1 - i)*2ⁱ) * Tⁱ` is the power | |
series of `f(T)/(T⁻¹-2)`, and the reason it behaves reasonsbly is the | |
assumption that T⁻¹-2 has a simple zero at 2⁻¹ and no other zeros in | |
the disc radius `r`. | |
### Implementation detail | |
In Lean the second sum is `∑' (n : ℤ), ∥ite (d ≤ n)` | |
`((finset.range (n - d).nat_abs.succ).sum (λ (l : ℕ), f (n - 1 - ↑l) * 2 ^ l))` | |
`0∥₊ * r ^ n`. | |
### The maths proof | |
∑(n ≥ d) ∥∑(0≤i≤(n-d)) f(n - 1 - i)*2ⁱ∥ * r^n | |
= ∑(n ≥ d) ∥∑(i≥0) f(n - 1 - i)2ⁱ∥ * rⁿ (as f(n-1-i) vanishes for i larger than n-d) | |
= ∑(n ≥ d) ∥(i<0) f(n - 1 - i)2ⁱ∥ * rⁿ (as sum f(x)2⁻ˣ=0) | |
= ∑(n ≥ d) ∥∑(k≥0) f(n + k) 2^(-1-k)∥ * rⁿ (set k=-1-i) | |
≤ ∑(n ≥ d) ∑(k≥0)∥ f(n+k)∥ 2^(-1-k) r^n (Cauchy-Schwarz) | |
= ∑(k≥0) ∑(n≥d) ∥f(n+k)∥2^(-1-k)r^n (turns out you can interchange the sums) | |
= 2⁻¹∑(k≥0) (∑(n≥d) ∥f(n+k)∥r^(n+k)) * (2r)^{-k} (rearranging) | |
≤ 2⁻¹∑(k≥0) c (2r)^{-k} (defining property of c) | |
= 2⁻¹ * c / (1-(2r)⁻¹) (sum of a GP) | |
= c * (2-r⁻¹)⁻¹ (rearranging) | |
### Comments on the maths proof | |
The logic in this proof is completely standard but needs a little thinking about | |
when formalising. Some of the manipulations we are doing in the earlier lines | |
of the proof (for example interchanging the sums) are only valid if the sum converges. | |
However ultimately the proof that the sum converges only happens on the last-but-one | |
line of the computation, where we prove that it's bounded above by something finite | |
(the sum of a GP). | |
There are several ways to fix this. | |
* One can go through the proof twice. In the first pass one can prove that everything | |
is `summable`, and then in the second pass one can then prove the results about equality | |
or boundedness of sums. This has the disadvantage that you have to do everything twice. | |
* Another approach is to write the proof once, but backwards; start with the sum of a geometric | |
progression and then go upwards through the maths proof above to deduce convergence and boundedness | |
of the original sum simultaneously. This has the mild disadvantage that you have to write | |
the proof backwards. | |
* A third approach would be to work not with `tsum` and `summable` at all, but to work | |
with `has_sum`. This has the disadvantage that you need to stop working with | |
equalities `∑a(n)=∑b(n)` or inequalities `∑a(n) ≤ ∑b(n)` and to start working with more complex | |
statements such as `has_sum a s ↔ has_sum b s` or `has_sum a s → ∃ t, has_sum b t ∧ t ≤ s`. | |
* The fourth approach avoids all of this. Instead of working with sums valued in `ℝ≥0` we | |
can work with sums taking values in `ℝ≥0∞` a.k.a. the interval `[0,∞]`. | |
## TODO | |
Switch to ennreal and then prove 6 lemmas for the first result. All the | |
summability results are in `thm69` so it's simply a case of | |
refactoring all of them. | |
-/ | |
lemma real.nnnorm_int (n : ℤ) : ∥(n : ℝ)∥₊ = ∥n∥₊ := | |
subtype.ext $ by simp [coe_nnnorm, real.norm_eq_abs, int.norm_eq_abs] | |
lemma real.neg_nnnorm_of_neg {r : ℝ} (hr : r < 0) : -(∥r∥₊ : ℝ) = r := | |
by rw [coe_nnnorm, neg_eq_iff_neg_eq, real.norm_eq_abs, abs_of_neg hr] | |
namespace psi_aux_lemma | |
/- | |
## The first lemma | |
-/ | |
open_locale ennreal | |
-- line 7 ≤ line 10 | |
lemma step7 {f : ℤ → ℝ} {d : ℤ} {r : ℝ≥0} (hr2 : 2⁻¹ < r) | |
(hconv : summable (λ (n : ℤ), ∥f n∥₊ * r ^ n)) : -- do I use hconv?? | |
∑' (b : ℕ), | |
(∑' (i : ℕ), | |
(∥f (d + ↑b + ↑i)∥₊ : ℝ≥0∞) * r ^ (d + b + i)) * | |
(2 * r)⁻¹ ^ b ≤ | |
2 * (↑(2 - r⁻¹)⁻¹ * ∑' (a : ℤ), ∥f a∥₊ * r ^ a) := | |
begin | |
have bound : ∀ (z : ℤ), ∑' (i : ℕ), (∥f (z + ↑i)∥₊ : ℝ≥0∞) * r ^ (z + ↑i) ≤ | |
∑' (a : ℤ), ∥f a∥₊ * r ^ a, | |
{ intro z, | |
refine tsum_le_tsum_of_inj (λ i, z + i) _ _ _ ennreal.summable ennreal.summable, | |
{ intros a b h, simpa using h, }, | |
{ intros, exact ennreal.zero_le', }, | |
{ intros, apply le_refl _ } }, | |
suffices : ∑' (b : ℕ), (∑' (a : ℤ), (∥f a∥₊ : ℝ≥0∞) * r ^ a) * (2 * ↑r)⁻¹ ^ b = | |
2 * (↑(2 - r⁻¹)⁻¹ * ∑' (a : ℤ), ↑∥f a∥₊ * ↑r ^ a), | |
{ rw ← this, | |
apply ennreal.tsum_le_tsum, | |
intro a, | |
apply ennreal.mul_le_mul_of_right, | |
apply bound }, | |
rw [ennreal.tsum_mul_left, mul_comm, ← mul_assoc], | |
congr, | |
rw ennreal.tsum_geometric, | |
apply ennreal.inv_eq_of_mul_eq_one, | |
rw ← mul_assoc, | |
have hr : 0 < 2 - r⁻¹, | |
{ rw nnreal.sub_pos, | |
exact nnreal.inv_lt_of_inv_lt (by norm_num) hr2, }, | |
rw ennreal.coe_inv hr.ne', | |
apply ennreal.mul_inv_eq_of_eq_mul (by exact_mod_cast hr.ne') ennreal.coe_ne_top, | |
rw [ennreal.sub_mul, one_mul, one_mul, ennreal.coe_sub], | |
{ congr, | |
refine ennreal.mul_eq_of_mul_inv_eq (by norm_num) (by norm_num) _, | |
rw [ennreal.mul_inv, mul_comm, ennreal.coe_inv], | |
{ refine (lt_of_le_of_lt (by norm_num) hr2).ne', }, | |
{ left, norm_num, }, | |
{ left, norm_num, }, }, | |
{ intros, norm_num, } | |
end | |
-- line 5 ≤ line 10 | |
lemma step6 {f : ℤ → ℝ} {d : ℤ} {r : ℝ≥0} (hr2 : 2⁻¹ < r) (hdf : ∀ n, n < d → f n = 0) | |
(hconv : summable (λ n : ℤ, ∥f n∥₊ * r ^ n)) : | |
(2⁻¹ : ℝ≥0∞) * ∑' (i j : ℕ), ↑∥f (d + ↑i + ↑j) * 2⁻¹ ^ j∥₊ * ↑(r ^ (d + ↑i)) ≤ | |
↑(2 - r⁻¹)⁻¹ * ∑' (a : ℤ), ↑(∥f a∥₊ * r ^ a) := | |
begin | |
rw ennreal.tsum_comm, | |
-- woohoo, I just interchanged the sums | |
simp_rw [nnnorm_mul, nnnorm_pow, ennreal.coe_mul, | |
ennreal.coe_zpow (lt_of_le_of_lt zero_le' hr2).ne'], | |
push_cast, | |
simp only [nnnorm_inv, real.nnnorm_two, ennreal.coe_inv, ne.def, bit0_eq_zero, one_ne_zero, | |
not_false_iff, ennreal.coe_bit0, ennreal.coe_one], | |
have h2ne0 : (2 : ℝ≥0∞) ≠ 0 := by norm_num, | |
have h2netop : (2 : ℝ≥0∞) ≠ ⊤ := by norm_num, | |
have hrne0 : (r : ℝ≥0∞) ≠ 0, | |
{ norm_cast, | |
refine (lt_of_le_of_lt _ hr2).ne', | |
norm_num }, | |
have hrnetop : (r : ℝ≥0∞) ≠ ⊤ := ennreal.coe_ne_top, | |
rw ennreal.inv_mul_le_iff h2ne0 h2netop, | |
have : ∀ a b : ℕ, (∥f (d + ↑a + ↑b)∥₊ : ℝ≥0∞) * 2⁻¹ ^ b * ↑r ^ (d + ↑a) = | |
∥f (d + ↑a + ↑b)∥₊ * r ^ (d + a + b) * (2 * r)⁻¹ ^ b, | |
{ intros a b, | |
rw [ennreal.mul_inv (or.inl h2ne0) (or.inl h2netop), mul_pow, ← zpow_coe_nat (↑r)⁻¹], | |
rw ennreal.zpow_add hrne0 hrnetop _ b, | |
have : (∥f (d + ↑a + ↑b)∥₊ : ℝ≥0∞) * (↑r ^ (d + ↑a) * ↑r ^ (b : ℤ)) * (2⁻¹ ^ b * (↑r)⁻¹ ^ (b : ℤ)) = | |
↑∥f (d + ↑a + ↑b)∥₊ * 2⁻¹ ^ b * ↑r ^ (d + ↑a) * (r ^ (b : ℤ) * r⁻¹ ^ (b : ℤ)), | |
{ ring }, | |
rw this, | |
convert (mul_one _).symm, | |
rw ← ennreal.coe_inv (by exact_mod_cast hrne0), | |
norm_cast, | |
rw ← mul_pow, | |
rw mul_inv_cancel (by exact_mod_cast hrne0), | |
apply one_pow }, | |
simp_rw [this, ennreal.tsum_mul_right, add_right_comm], | |
exact step7 hr2 hconv, | |
end | |
-- auxiliary convergence lemma | |
lemma step5 {f : ℤ → ℝ} {d : ℤ} {r : ℝ≥0} (hr2 : 2⁻¹ < r) (hdf : ∀ n, n < d → f n = 0) | |
(hconv : summable (λ n : ℤ, ∥f n∥₊ * r ^ n)) : | |
summable (λ (x : ℤ), f x * 2⁻¹ ^ x) := | |
begin | |
rw ← summable_subtype_and_compl, | |
change summable (λ x : {n : ℤ | n < 0}, _) ∧ _, | |
split, | |
{ let F : finset ↥{n : ℤ | n < 0} := finset.preimage (finset.Ico d 0 : finset ℤ) coe | |
(set.inj_on_of_injective subtype.coe_injective _), | |
apply summable_of_ne_finset_zero, | |
rintro b (hb : b ∉ F), | |
convert zero_mul _, | |
apply hdf, | |
by_contra hbd, push_neg at hbd, | |
apply hb, | |
rw finset.mem_preimage, | |
rw finset.mem_Ico, | |
exact ⟨hbd, b.2⟩ }, | |
{ apply summable_of_summable_nnnorm, | |
have := nnreal.summable_subtype hconv {n : ℤ | n < 0}ᶜ, | |
refine nnreal.summable_of_le _ this, | |
rintro ⟨b, hb : ¬ b < 0⟩, | |
push_neg at hb, | |
rw nnnorm_mul, | |
suffices : ∥f b∥₊ * (2 ^ b)⁻¹ ≤ ∥f b∥₊ * r ^ b, | |
{ simpa }, | |
apply nnreal.mul_le_mul_left, | |
rw ← inv_zpow, | |
apply nnreal.zpow_le_zpow' hb hr2.le, }, | |
end | |
example (r : ℝ≥0) (n : ℕ) : r ^ (n : ℤ) = r ^ n := zpow_coe_nat r n | |
noncomputable instance xxx : div_inv_monoid ℝ≥0 := infer_instance | |
-- second line is third line | |
lemma step4 {f : ℤ → ℝ} {n d : ℤ} {r : ℝ≥0} (hr1 : r < 1) (hr2 : 2⁻¹ < r) | |
(hdf : ∀ n, n < d → f n = 0) | |
(hconv : summable (λ n : ℤ, ∥f n∥₊ * r ^ n)) (hzero : ∑' n, f n * 2⁻¹ ^ n = 0) : | |
∑' (l : ℕ), f (n - 1 - ↑l) * 2 ^ l = 2⁻¹ * -∑' (m : ℕ), f (n + m) * 2⁻¹ ^ m := | |
begin | |
have : ∀ l : ℕ, (2 : ℝ) ^ l = 2⁻¹ ^ (n - 1 - l) * (2⁻¹ * 2 ^ n), | |
{ intro l, | |
rw [inv_zpow, ← zpow_neg, ← zpow_neg_one, ← zpow_coe_nat], | |
push_cast, | |
rw ← zpow_add₀ (two_ne_zero : (2 : ℝ) ≠ 0), | |
rw ← zpow_add₀ (two_ne_zero : (2 : ℝ) ≠ 0), | |
ring_nf, }, | |
conv_lhs begin | |
congr, | |
funext, | |
rw [this, ← mul_assoc], | |
end, clear this, | |
rw tsum_mul_right, | |
have : ∀ m : ℕ, (2⁻¹ : ℝ) ^ m = 2⁻¹ ^ (n + m) * 2 ^ n, | |
{ intro m, | |
rw [inv_zpow, ← zpow_neg, ← zpow_coe_nat, ← zpow_add₀ (two_ne_zero : (2 : ℝ) ≠ 0), | |
inv_zpow, ← zpow_neg], | |
ring_nf, }, | |
conv_rhs begin | |
congr, skip, | |
congr, | |
congr, | |
funext, | |
rw [this, ← mul_assoc], | |
end, clear this, | |
rw [mul_comm, mul_assoc, tsum_mul_right, ← neg_mul, mul_comm ((2 : ℝ) ^ n)], | |
congr, | |
rw [eq_neg_iff_add_eq_zero, add_comm, ← hzero, | |
← tsum_add_tsum_compl ((step5 hr2 hdf hconv).comp_injective subtype.coe_injective : | |
summable ((_ : ℤ → ℝ) ∘ (coe : {z : ℤ | n ≤ z} → ℤ))) | |
((step5 hr2 hdf hconv).comp_injective subtype.coe_injective)], | |
{ congr' 1, | |
{ rw ← ((nat.equiv_le_int n).tsum_eq : _ → (_ : ℝ) = _), | |
congr', ext b, | |
rw add_comm n, | |
refl, }, | |
{ rw ← ((nat.equiv_le_int_compl n).tsum_eq : _ → (_ : ℝ) = _), | |
congr', ext b, | |
rw (show n - 1 - b = n - (b + 1), by ring), | |
refl, } }, | |
end | |
-- second line ≤ last line | |
lemma step3 {f : ℤ → ℝ} {r : ℝ≥0} (hr1 : r < 1) (hr2 : 2⁻¹ < r) {d : ℤ} | |
(hdf : ∀ n, n < d → f n = 0) (hconv : summable (λ n : ℤ, ∥f n∥₊ * r ^ n)) | |
(hzero : ∑' n, f n * 2⁻¹ ^ n = 0) : | |
∑' (n : ℤ), ((∥ite (d ≤ n) (∑' (l : ℕ), f (n - 1 - ↑l) * 2 ^ l) 0∥₊ * r ^ n : ℝ≥0) : ℝ≥0∞) ≤ | |
((2 - r⁻¹)⁻¹ * ∑' (n : ℤ), ∥f n∥₊ * r ^ n : ℝ≥0) := | |
begin | |
simp_rw step4 hr1 hr2 hdf hconv hzero, | |
-- n - d = m | |
rw tsum_eq_tsum_of_ne_zero_bij (λ m : function.support | |
(λ m : ℕ, ((∥(2⁻¹ : ℝ) * (-∑' (l : ℕ), f (d + m + ↑l) * 2⁻¹ ^ l)∥₊ * r ^ (d + m) : ℝ≥0) : ℝ≥0∞)), | |
d + m.1), | |
{ dsimp only, | |
simp_rw [nnnorm_mul, nnnorm_neg], | |
push_cast, | |
simp only [nnnorm_inv, real.nnnorm_two, ennreal.coe_inv, ne.def, bit0_eq_zero, one_ne_zero, | |
not_false_iff, ennreal.coe_bit0, ennreal.coe_one], | |
have summable_half : ∀ t : ℤ, summable (λ (x : ℕ), f (t + ↑x) * 2⁻¹ ^ x), | |
{ intro t, | |
rw summable_mul_right_iff (show (2 : ℝ)⁻¹ ^ t ≠ 0, from zpow_ne_zero _ (by norm_num)), | |
simp_rw [mul_assoc, ← zpow_coe_nat], | |
simp_rw [← zpow_add₀ (show (2 : ℝ)⁻¹ ≠ 0, by norm_num), add_comm _ t], | |
exact (step5 hr2 hdf hconv).comp_injective (show function.injective (λ x : ℕ, t + x), | |
by {intros x y hxy, simpa using hxy, }), }, | |
suffices : | |
∑' (m : ℕ), (2⁻¹ : ℝ≥0∞) * ↑(∑' (l : ℕ), ∥f (d + ↑m + ↑l) * (2⁻¹ ^ l)∥₊ : ℝ≥0) * | |
↑(r ^ (d + ↑m)) ≤ ↑(2 - r⁻¹)⁻¹ * ↑∑' (n : ℤ), ∥f n∥₊ * r ^ n, | |
{ refine le_trans _ this, | |
apply ennreal.tsum_le_tsum, | |
intro m, | |
apply ennreal.mul_le_mul_of_right, | |
apply ennreal.mul_le_mul_of_left, | |
norm_cast, | |
apply nnnorm_tsum_le, | |
rw ← nnreal.summable_iff_summable_nnnorm, | |
apply summable_half, }, | |
rw ennreal.coe_tsum hconv, dsimp only, | |
conv_lhs begin | |
congr, | |
funext, | |
rw ennreal.coe_tsum (show summable (λ (l : ℕ), ∥f (d + m + ↑l) * 2⁻¹ ^ l∥₊), begin | |
rw ← nnreal.summable_iff_summable_nnnorm, | |
apply summable_half, end), | |
end, | |
dsimp only, | |
simp_rw mul_assoc, | |
rw ennreal.tsum_mul_left, | |
simp_rw ← ennreal.tsum_mul_right, | |
apply step6 hr2 hdf hconv, }, | |
{ rintro ⟨x, _⟩ ⟨y, _⟩ h, | |
have hxy : x = y, | |
{ simpa using h }, | |
subst hxy }, | |
{ rintro n hn, | |
rw function.mem_support at hn, | |
split_ifs at hn with hdn, | |
{ rw set.mem_range, | |
let m := (n - d).nat_abs, | |
have hm : d + m = n, | |
{ apply add_eq_of_eq_sub', | |
rw [int.nat_abs_of_nonneg], | |
exact sub_nonneg.mpr hdn, }, | |
refine ⟨⟨m, _⟩, hm⟩, | |
rw function.mem_support, | |
convert hn, | |
rw hm, }, | |
{ exfalso, | |
apply hn, | |
simp, } }, | |
{ simp, }, | |
end | |
-- first line equals second line | |
lemma step2 {f : ℤ → ℝ} {n d : ℤ} (hn : d ≤ n) (hdf : ∀ n, n < d → f n = 0) : | |
(finset.range (n - d).nat_abs.succ).sum (λ (l : ℕ), f (n - 1 - ↑l) * 2 ^ l) = | |
∑' (l : ℕ), f (n - 1 - l) * 2 ^ l := | |
begin | |
apply (tsum_eq_sum _ : (_ : ℝ) = _).symm, | |
intros b hb, | |
convert zero_mul ((2 : ℝ) ^ b), | |
apply hdf, | |
by_contra hbd, | |
push_neg at hbd, | |
apply hb, | |
rw [finset.mem_range, nat.lt_succ_iff], | |
suffices : (b : ℤ) ≤ ((n - d).nat_abs : ℤ), | |
{ assumption_mod_cast, }, | |
rw ← int.eq_nat_abs_of_zero_le; | |
linarith, | |
end | |
-- coerce to ℝ≥0∞ | |
lemma step1 {f : ℤ → ℝ} {r : ℝ≥0} (hr1 : r < 1) (hr2 : 2⁻¹ < r) {d : ℤ} | |
(hdf : ∀ n, n < d → f n = 0) (hconv : summable (λ n : ℤ, ∥f n∥₊ * r ^ n)) | |
(hzero : ∑' n, f n * 2⁻¹ ^ n = 0) : | |
∑' (n : ℤ), | |
((∥ite (d ≤ n) ((finset.range (n - d).nat_abs.succ).sum (λ (l : ℕ), f (n - 1 - ↑l) * 2 ^ l)) 0∥₊ * | |
r ^ n : ℝ≥0) : ℝ≥0∞) ≤ | |
((2 - r⁻¹)⁻¹ * ∑' (n : ℤ), ∥f n∥₊ * r ^ n : ℝ≥0) := | |
begin | |
have : ∀ n, | |
∥ite (d ≤ n) ((finset.range (n - d).nat_abs.succ).sum (λ (l : ℕ), f (n - 1 - ↑l) * 2 ^ l)) 0∥₊ * r ^ n | |
= | |
∥ite (d ≤ n) (∑' (l : ℕ), f (n - 1 - l) * 2 ^ l) 0∥₊ * r ^ n, | |
{ intro n, | |
congr' 2, | |
split_ifs with hn, | |
{ rw step2 hn hdf }, | |
{ refl } }, | |
simp_rw this, | |
apply step3 hr1 hr2 hdf hconv hzero, | |
end | |
-- first line ≤ last line | |
lemma key_tsum_lemma (f : ℤ → ℝ) (r : ℝ≥0) (hr1 : r < 1) (hr2 : 2⁻¹ < r) (d : ℤ) | |
(hdf : ∀ n, n < d → f n = 0) (hconv : summable (λ n : ℤ, ∥f n∥₊ * r ^ n)) | |
(hzero : ∑' n, f n * 2⁻¹ ^ n = 0) : | |
∑' (n : ℤ), ∥ite (d ≤ n) ((finset.range (n - d).nat_abs.succ).sum | |
(λ (l : ℕ), f (n - 1 - ↑l) * 2 ^ l)) 0∥₊ * r ^ n ≤ | |
(2 - r⁻¹)⁻¹ * ∑' n, ∥f n∥₊ * r ^ n := | |
begin | |
have := step1 hr1 hr2 hdf hconv hzero, | |
have this2 : ∑' (n : ℤ), | |
(((∥ite (d ≤ n) ((finset.range (n - d).nat_abs.succ).sum (λ (l : ℕ), f (n - 1 - ↑l) * 2 ^ l)) 0∥₊ * | |
r ^ n) : ℝ≥0) : ℝ≥0∞) < ⊤, | |
{ refine lt_of_le_of_lt this _, | |
exact ennreal.coe_lt_top, | |
}, | |
have this3 : summable (λ n, ((∥ite (d ≤ n) ((finset.range (n - d).nat_abs.succ).sum (λ (l : ℕ), f (n - 1 - ↑l) * 2 ^ l)) 0∥₊ * | |
r ^ n) : ℝ≥0)) := ennreal.tsum_coe_ne_top_iff_summable.mp this2.ne, | |
rw ← ennreal.coe_le_coe, | |
convert this, | |
apply ennreal.coe_tsum this3, | |
end | |
end psi_aux_lemma | |
/- | |
## The second lemma | |
-/ | |
namespace theta_aux_lemma | |
-- Here is the fact which Clausen/Scholze need for the application to "splitting θ | |
-- in a bounded way". | |
theorem tsum_le (r : ℝ≥0) {s : ℝ≥0} (hs0 : 0 < s) (hs : s < 1) : | |
∑' (n : ℤ), (nnreal.int.binary r n : ℝ≥0) * s ^ n ≤ | |
s ^ ⌈real.log r / real.log (2⁻¹ : ℝ≥0)⌉ * (1 - s)⁻¹ := | |
begin | |
let d := ⌈real.log r / real.log (2⁻¹ : ℝ≥0)⌉, | |
rw mul_comm, | |
rw ← nnreal.int.tsum_add_tsum_compl' {n : ℤ | n < d} (nnreal.int.binary_summable r hs), | |
have h0 : ∑' (x : ↥{n : ℤ | n < d}), (λ (n : ℤ), ↑(nnreal.int.binary r n) * s ^ n) ↑x = 0, | |
{ convert (tsum_zero : _ = (0 : ℝ≥0)), ext ⟨n, hn : n < d⟩, | |
simp [nnreal.int.binary_eq_zero r n hn] }, | |
rw [h0, zero_add], clear h0, | |
rw ← (nat.equiv_int_lt_compl d).tsum_eq, swap, apply_instance, | |
simp only [nat.equiv_int_lt_compl, zpow_add₀ hs0.ne', ←mul_assoc, equiv.coe_fn_mk, subtype.coe_mk, | |
zpow_coe_nat, nonneg.coe_one, nnreal.tsum_mul_right], | |
rw mul_le_mul_right₀ (zpow_ne_zero _ hs0.ne'), | |
rw ← tsum_geometric_nnreal hs, | |
refine nnreal.tsum_le_tsum (λ n, _) (nnreal.summable_geometric hs), | |
apply mul_le_of_le_one_left', | |
norm_cast, | |
apply nnreal.int.binary_le_one, | |
end | |
end theta_aux_lemma | |
-- is `summable_subtype_and_compl` true for add_comm_monoids? Why is it stated for groups? | |